Young adults' responses to alternative messages describing a sugar-sweetened beverage price increase. Issue 1 (28th July 2016) - Gollust, Sarah E; Tang, Xuyang; White, James M; French, Simone A; Runge, Carlisle Ford; Rothman, Alexander J
Abstract: Objective: Many jurisdictions in the USA and globally are considering raising the prices of sugar-sweetened beverages (SSB) through taxes as a strategy to reduce their consumption. The objective of the present study was to identify whether the rationale provided for an SSB price increase affects young adults' behavioural intentions and attitudes towards SSB. Design: Participants were randomly assigned to receive one of eight SSB price increase rationales. Intentions to purchase SSB and attitudes about the product and policy were measured. Setting: A forty-six-item cross-sectional Internet survey. Subjects: Undergraduate students ( n 494) at a large US Midwestern university. Results: Rationale type was significantly associated with differences in participants' purchasing intentions for the full sample ( F 7, 485 =2·53, P =0·014). Presenting the rationale for an SSB price increase as a user fee, an effort to reduce obesity, a strategy to offset health-care costs or to protect children led to lower SSB purchasing intentions compared with a message with no rationale. Rationale type was also significantly associated with differences in perceptions of soda companies ( F 7, 485 =2·10, P =0·043); among low consumers of SSB, messages describing the price increase as a user fee or tax led to more negative perceptions of soda companies. Conclusions: The rationale attached to an SSB price increase could influence consumers. However, these message effects may depend on individuals' level of SSB consumption.